2010
DOI: 10.1159/000322093
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Polymorphism and Dementia: A Hospital-Based Study from Southern India

Abstract: Background/Aims: To evaluate the ApoE gene polymorphism among patients with dementia from southern India. Methods: Persons with dementia attending a geriatric clinic in a hospital setting located in southern India and matched controls were recruited. All subjects were evaluated on standard assessments and were diagnosed according to the ICD-10; genotyping was done at the apolipoprotein E (ApoE) locus. Results: The study comprised 212 cases and 195 controls. The ApoE4 allele was significantly more prevalent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…This was the largest study, comprising 419 patients with dementia and 138 age-matched controls, when compared to the other Indian studies done so far [24,33,34,40]. Regarding the genetic factors analysed in the cohort, a strong positive association was established between the APOE ε4 allele and AD, which is in concordance with previous reports worldwide.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was the largest study, comprising 419 patients with dementia and 138 age-matched controls, when compared to the other Indian studies done so far [24,33,34,40]. Regarding the genetic factors analysed in the cohort, a strong positive association was established between the APOE ε4 allele and AD, which is in concordance with previous reports worldwide.…”
Section: Discussionsupporting
confidence: 88%
“…39.42% for the AD group and 17.75% for the controls. These figures are higher than those from the single southern Indian report [24]. It has been reported that amyloid pathology and tau pathology are interlinked, and are quite complementary to one another, leading to neurodegeneration in AD [35].…”
Section: Discussionmentioning
confidence: 76%
“…[30] However, a clinic-based study from South India confirmed the increased frequency of ApoE4 in patients with dementia (0.18), especially among those with AD (0.21), and also in VaD. [31] The frequency was higher than that reported in the other rural community-based study from North India (0.15 in all dementias) and the hospital-based study. A study from Central India has shown positive influence of presenilin gene (PS1, allele 1) and ApoE gene e-4 alleles, increasing the susceptibility for degenerative dementia as compared to VaD.…”
Section: Genetics Of Dementia In Indiamentioning
confidence: 82%
“…A recent study reported widespread reduction in FA in both young and elderly ApoE 4 carriers without significant differential changes with age [7] . These differences could be due to sample size effects, and geographical and population variability in ApoE 4 frequency [15] . Brain atrophy in AD seems to be influenced by ApoE, and it has been observed that greater 4 load is associated with increased susceptibility of the temporal cortex, amygdala and limbic regions [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…DTI was acquired in 32 directions at b values of 0 and 1,000 using a Philips Achieva 3-tesla MRI scanner. The subjects who participated in the present study were recruited as part of larger ongoing studies at the clinic [15] .…”
Section: Methodsmentioning
confidence: 99%